Single High Posterolateral Portal Suture Anchor Repair for Lateral Meniscal Root Tears in Adolescents - Wittawat Boonyanuwat, M.D.; Komson Plangsiri, M.D.; Pinkawas Kongmalai, M.D. (Arthroscopy Techniques)
Meniscal root tears, especially in the posterior root of the lateral meniscus, are critical injuries that can lead to altered knee mechanics and early-onset osteoarthritis if left untreated. In adolescents, these injuries present additional challenges due to the risk of growth plate disturbances associated with traditional repair techniques. This Technical Note describes a refined arthroscopic technique for lateral meniscal root repair in adolescents, utilizing a single high posterolateral portal for suture anchor placement. The technique emphasizes safety by using the fibular head as an external landmark to avoid peroneal nerve injury and ensures precise anatomic placement of the suture anchor without the need for a transosseous tibial tunnel. We detail the procedural steps, including portal creation, anchor insertion, and postoperative care, highlighting the advantages of this approach, such as reduced risk of physeal injury and simplified surgical execution. This technique provides a promising and safer alternative for the management of lateral meniscal root tears in the adolescent population.